Respon Masyarakat Non Muslim Kota Kualasimpang Terhadap Pemberlakuan Qanun Nomor 11 Tahun 2018 Tentang Lembaga Keuangan Syariah - Rafiza Zuliani; Purnama, Rahma Amelia; Agustinar, Agustinar (AT-TASYRI’: JURNAL ILMIAH PRODI MUAMALAH, 2024)
The aim of this research is to determine the implementation of Qanun Number 11 of 2018 concerning Sharia Financial Institutions, the response of the non-Muslim community in Kualasimpang regarding Qanun Number 11 of 2018 concerning Sharia Financial Institutions and the obstacles faced by the community with the implementation of Qanun Number 11 of 2018.This type of research is field research with a qualitative descriptive approach. This research was conducted in Kualasimpang City District, Aceh Tamiang Regency. The subjects in this research were non-Muslim communities in Kualasimpang with a total of 10 informants. The data sources in this research are primary and secondary data. Primary data is data obtained directly from research informants, while secondary data is data obtained from literature reviews such as journals and books related to the title of this research. The data collection instruments in this research were observations and interviews conducted with all informants in the research. The data analysis technique in this research uses the Miles and Huberman model with stages of data reduction, data display and verification/conclusion.From the research results it can be explained thatThe implementation of Qanun Number 11 of 2018 has pros and cons, especially for non-Muslim communities. The obstacle felt by non- Muslim communities when using transactions at Islamic banks is that they often go offline, which hinders their activities, especially for non-Muslim communities who work as business people. They also think that conventional banks have never experienced such problems, but they feel that this is currently happening to Islamic banks.Some non-Muslim communities in Kualasimpang object to the implementation of Qanun regarding sharia financial institutions. They argue that by using sharia banks it is difficult for them to make transactions.The opinion of the Qanun designer regrets the implementation of Qanun Number 11 of 2018 because it has a big impact on transactions for both Muslim and non-Muslim communities, especially in Kualasimpang City District, Aceh Tamiang Regency.